146k views
5 votes
Cara evaluated the expression below. StartFraction 4 (7 minus 13) over 3 EndFraction + (negative 4) squared minus 2 (6 minus 2) = StartFraction 28 minus 13 over 3 EndFraction + (negative 4) squared minus 2 (4) = StartFraction 15 over 3 EndFraction + 16 minus 18 = 5 + 16 minus 8 = 13.

2 Answers

5 votes

Answer:

A.

Explanation:

im taking the quiz

User HJW
by
5.3k points
7 votes

Answer:

In shorter terms of the answer above me, the Answer is Choice A.

Explanation:

Hope that summed it up!!

User Clement
by
4.4k points